Aion is a bistable anion-conducting channelrhodopsin that provides temporally extended and reversible neuronal silencing - Rodriguez-Rozada, Silvia; Wietek, Jonas; Tenedini, Federico; Sauter, Kathrin; Dhiman, Neena; Hegemann, Peter; Soba, Peter; Wiegert, J. Simon (Communications Biology, 2022)
Optogenetic silencing allows to reveal the necessity of selected neuronal populations for various neurophysiological functions. These range from synaptic transmission and coordinated neuronal network activity to control of specific behaviors. An ideal single-component optogenetic silencing tool should be switchable between active and inactive states with precise timing while preserving its activity in the absence of light until switched to an inactive state. Although bistable anion-conducting channelrhodopsins (ACRs) were previously engineered to reach this goal, their conducting state lifetime was limited to only a few minutes and some ACRs were not fully switchable. Here we report Aion, a bistable ACR displaying a long-lasting open state with a spontaneous closing time constant close to 15 min. Moreover, Aion can be switched between the open and closed state with millisecond precision using blue and orange light, respectively. The long conducting state enables overnight silencing of neurons with minimal light exposure. We further generated trafficking-optimized versions of Aion, which show enhanced membrane localization and allow precisely timed, long-lasting all-optical control of nociceptive responses in larvae of Drosophila melanogaster. Thus, Aion is an optogenetic silencing tool for inhibition of neuronal activity over many hours which can be switched between an active and inactive state with millisecond precision.
CRIS-Team Scopus Importer:2022-07-22